PROFILE OF BLUNT INJURY OF EYE - A HOSPITAL BASED STUDY - PRAGATI GARG; RUBII MALHOTRA; LUXMI SINGH; ANURAG KUMAR SINGH (International Journal of Pharma and Bio Sciences, 2014)
The study was conducted from June 2010 – May 2012. Detailed history with special reference to age, sex, and mode of injury, causes and circumstances of trauma were recorded. Ocular examination done to assess causes and level of loss of vision. B-scan was done for the posterior segment. The patients were followed up for 3 months. There were 76 patients of blunt ocular trauma (63.16% males &36.84% females), mean age 20.02 yr. Right eye was more commonly involved (p=0.02). Commonest trauma was occupational (39.47%) and commonest trauma causing agent was wood (35.52%) (vegetative material 19.73%, wood stick 10.12% & pencil 5.2%) (p=0.04%). 53.94% eyes had visual acuity of 0.1-0.6 log mar. Commonest cause of diminution of vision after 3 months was cataract 31.63% (p=0.05). More eye care programs are needed to educate about ocular safety and hence reducing blindness due to ocular trauma.